Structured Annual Faculty Review Program Accelerates Professional Development and Promotion - Stanley J. Robboy MD; Roger McLendon MD (Elsevier, 2017)
This retrospective observational study on faculty development analyzes the Duke University Pathology Department's 18-year experience with a structured mentoring program involving 51 junior faculty members. The majority had MD degrees only (55%). The percentage of young women faculty hires before 1998 was 25%, increasing to 72% after 2005. Diversity also broadened from 9% with varied heritages before 1998 to 37% since then. The mentoring process pivoted on an annual review process. The reviews generally helped candidates focus much earlier, identified impediments they individually felt, and provided new avenues to gain a national reputation for academic excellence. National committee membership effectively helped gain national exposure. Thirty-eight percent of the mentees served on College of American Pathologists (CAP) committees, exponential multiples of any other national society. Some used CAP resources to develop major programs, some becoming nationally and internationally recognized for their academic activities. Several faculty gained national recognition as thought leaders for publishing about work initiated to serve administrative needs in the Department. The review process identified the need for more protected time for research, issues with time constraints, and avoiding exploitation when collaborating with other departments. This review identified a rigorous faculty mentoring and review process that included annual career counseling, goal-oriented academic careers, monitored advancement to promotion, higher salaries, and national recognition. All contributed to high faculty satisfaction and low faculty turnover. We conclude that a rigorous annual faculty review program and its natural sequence, promotion, can greatly foster faculty satisfaction.